Risk control in Jackleg drilling in underground mining - Concepción Gamarra, Jorge Luis (2022)
The objective of this research was to reduce the levels of risks to which the drilling master miner and the drilling assistant miner are exposed using Jackleg pneumatic machines in underground mining, it contributes to applicate the controls associated with the planning, execution, monitoring and improvement of this activity, to achieve safety and healthy workplaces. The research is descriptive and explanatory, and the methodology implements the observation of drilling fronts activity in underground mining. The research was developed in Compañía Minera Castrovirreyna S.A. The results obtained show that who work in drilling fronts with Jackleg pneumatic machines are mainly exposed to the following risks: rock falls, hand-arm vibrations, falls to the same level, material impact, entrapment by moving parts and knock down by moving equipment. The application of the proposed controls for this activity has resulted in 64% low residual risks and 36% medium residual risks.